Kelly Comfort and Marylaura Papalas, editors. New Directions in Flânerie: Global Perspectives for the Twenty-First Century. Routledge, 2022. - Emily Hall (Studies in 20th & 21st Century Literature, 2023)
Review of Kelly Comfort and Marylaura Papalas, editors. New Directions in Flânerie: Global Perspectives for the Twenty-First Century. Routledge, 2022. 273 pp.
Keywords: Flanerie; Walking; Global; Twenty-First Century; Comparative Literature; Urbanity